1997
DOI: 10.1161/01.atv.17.11.2383
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis After Stent Implantation Compared With Balloon Angioplasty in Rabbits

Abstract: Both cell proliferation and apoptosis (programmed cell death) are supposed to play a role in restenosis after angioplasty. We studied these processes in smooth muscle cells (SMCs) and macrophages 1, 4, and 12 weeks after balloon angioplasty or Palmaz-Schatz stent implantation in rabbit iliac arteries. Proliferating cells were visualized by immunostaining with antibodies directed against proliferating cell nuclear antigen. Apoptotic cells were detected using the TUNEL (terminal deoxynucleotidyl transferase-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 22 publications
3
43
1
1
Order By: Relevance
“…5,16,17 The impact of monocytes and macrophages on vascular repair of stented blood vessels is considered even more significant. Macrophage content in the vessel wall is markedly higher and prolonged in stented versus balloon-injured arteries, 8,10 and it correlates with neointimal formation. 10 Furthermore, the contribution of neointimal formation, which is mediated via innate immunity, to in-stent restenosis outweighs its role in restenosis after balloon injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,16,17 The impact of monocytes and macrophages on vascular repair of stented blood vessels is considered even more significant. Macrophage content in the vessel wall is markedly higher and prolonged in stented versus balloon-injured arteries, 8,10 and it correlates with neointimal formation. 10 Furthermore, the contribution of neointimal formation, which is mediated via innate immunity, to in-stent restenosis outweighs its role in restenosis after balloon injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although recoil and remodeling are negligible, local inflammation and regional neointimal formation are greater than that observed after balloon angioplasty. 6,7 Macrophage accumulation is increased in stented arteries compared with balloon-injured vessels, [7][8][9] with tissue macrophage content linearly correlating with neointimal area, suggesting a pivotal role for monocytes and macrophages in stent restenosis. 10 Bisphosphonates (BPs), widely used in treating osteoporosis and other bone diseases, are potent inhibitors of osteoclasts.…”
mentioning
confidence: 99%
“…Macrophage accumulation has been observed to be the major inflammatory response in stented arteries both in rabbits and primates. [15][16][17][18] In addition, several animal studies have demonstrated an ability to reduce neointima formation in stented arteries using anti-inflammatory strategies including antibodymediated blocking of Mac1 binding, blockade of the MCP-1 receptor CCR2 and immunosuppression by intravenous injection of IL-10. 15,16,18 Our ability to transduce immune cells with marker gene is also suggestive of sustained gene transfer in vivo, since macrophage accumulation in stented vessel segments is the result of a time-dependent process involving monocyte attachment, extravasation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This unique characteristic of polymer-coated stent delivery provides a new capability to the vascular gene therapy field to modulate the activity of immune cells that are believed to be a significant contributing factor to in-stent restenosis. [15][16][17][18] Results A number of nondegradable polymer matrix materials are currently being evaluated for coating stents. Of those, polyurethane has been shown to be effective in coating stents to prevent the thrombosis that can occur with uncoated stents and with some of the degradable polymers that have been tested in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Following a coronary intervention, the severety of the endothelial dysfunction may depend on the intensity of the injury, as well as on the specific type of the percutaneous intervention performed. The implantation of coronary endoprostheses, or stents, may cause more severe arterial injury 108,109 , and a more intense inflammatory response in the vascular wall than other percutaneous coronary interventions 110,111 , and be associated with incomplete endothelial regeneration 112 . Recent experimental evidence indicates that stent implantation may be associated with both more severe and prolonged endothelial dysfunction 113 .…”
Section: Clinical Implications -The Implications Of Endothelial Dysfumentioning
confidence: 99%